Performance assessment and influencing factors of human settlement improvement in traditional villages based on Balanced Scorecard theory: a case study of Jiaozuo, China - He, Yanbing; Yin, Chenjing; Mao, Xiaohu; Guo, Yanhua (Frontiers in Sustainable Food Systems, 2025)
Assessing the performance level of human settlement improvement in traditional villages is significant in promoting the protection of traditional villages, but there is a lack of performance research on human settlement improvement from the perspective of corporate governance in previous studies. This paper selected 16 traditional villages as case villages and obtained a total of 345 questionnaires. By reference to the Balanced Scorecard (BSC) theory, a performance evaluation index system for human settlement improvement is constructed in this paper. In addition, the level of performance exhibited by traditional villages is evaluated and analyzed via the entropy weight Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) method and the obstacle degree analysis method. This study reveals the following findings: (1) The performance level of traditional villages in Jiaozuo city ranges between 0.28 and 0.64, with an average value of 0.49, thus indicating a medium level. (2) With respect to the subdimensions of human settlement improvement performance, the policy management dimension (0.88) exhibits the highest value, followed by the villagers dimension (0.48) and the learning and growth dimension (0.27), while the financial benefits dimension (0.10) exhibits the lowest value. (3) The obstacles affecting the performance level of human settlement improvement in different types of traditional villages are characterized by both similarities and differences. This study summarized the effects of traditional village human settlement improvement, and provided more scientific and reliable governance suggestions for future traditional village human settlement improvement, so as to better promote the protection of traditional villages and the sustainable development of the human settlement environment.